2021
DOI: 10.1136/bmjopen-2021-048700
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve infant and young child feeding practices in Ethiopia: a systematic review

Abstract: ObjectiveIn Ethiopia, despite the implementation of several interventions to improve infant and young child feeding (IYCF) practices, no published studies have highlighted the most effective IYCF interventions in the country. This systematic review investigated the impacts of various interventions on IYCF in Ethiopia.Source of informationA systematic search was conducted on seven computerised bibliographic databases (Embase, ProQuest Central, Scopus, PsycINFO, Web of Science, MEDLINE/PubMed and CINAHL) to loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Exposure to more than one IYCF intervention delivering through different platforms has been proven to be more successful in improving IYCF outcomes compared with a single form of intervention delivered at a single setting. 4 Interventions delivered through multiple settings may have an increased intensity that can be translated into behavioural changes due to repeated contacts and adequate coverage of interventions. 36 Caregivers’ information sources in our study were 60% from health facilities and 10% from new media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to more than one IYCF intervention delivering through different platforms has been proven to be more successful in improving IYCF outcomes compared with a single form of intervention delivered at a single setting. 4 Interventions delivered through multiple settings may have an increased intensity that can be translated into behavioural changes due to repeated contacts and adequate coverage of interventions. 36 Caregivers’ information sources in our study were 60% from health facilities and 10% from new media.…”
Section: Discussionmentioning
confidence: 99%
“…It also reduces the risk of chronic non-communicable diseases, such as diabetes and cardiovascular disease, in later life. 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that large‐scale social and behaviour change communication interventions were linked to improvements in IYCF practices in Ethiopia (Kim et al, 2016 ). Interventions on IYCF practices should be done along the continuum of care, from conception until a child's second birthday (Ahmed et al, 2021 ). Having the IYCF message also come from HEWs or AEWs may help to reinforce the positive message and promote a healthy diet to children in a rural setting of Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…A three-stage search strategy was implemented to locate both peer-reviewed articles and grey literatures, consistent with prior systematic reviews (3032) . In stage one, we conducted a manual search to check for previously published systematic reviews of interventions on childhood malnutrition in Ethiopia.…”
Section: Methodsmentioning
confidence: 99%